Efficiency, effectiveness and economy in budget execution, Chimborazo health zone coordination - Puente Riofrío, Mariana Isabel; Tixi Torres, Jennifer Amparito; Arias González, Iván Patricio (mktDESCUBRE; Vol 1 No 19 (2022): Nineteenth Edition (January - June)DO - 10.36779/mktdescubre.v1i19.680, 2022)
The bad public management is a transcendental problem reflected in the budget execution, the present investigation had as objective to analyze the correlation between efficiency, effectiveness and economy in the budget execution of the Zonal Coordination 3-Health, Riobamba, of the 2019 period, the methodology was of mixed type because quantitative and qualitative data have been included, with a descriptive research scope because the research was based on the analysis and therefore on specifying properties, profiles of the officials of the case study entity and the characteristics of the processes for obtain the levels of the study variables, the techniques used during the investigative process were observation, interview and surveys to officials for the collection of information related to the budget, the data of the budget proforma and its execution of the budget were analyzed. fiscal year 2019, from which the correlation was applied Pearson ion to determine if there is any relationship between variables, determining that there is a significant relationship between economy - budget execution of 89.7%, efficiency - budget execution 88.8% and effectiveness - budget execution 90.3%, where it is concluded that the levels of efficiency, efficiency and economy show a positive correlation with the level of budget execution.